Assessment of chloroquine as a modulator of immune activation to improve CD4 recovery in immune nonresponding HIV‐infected patients receiving antiretroviral therapy. Issue 1 (2nd June 2014) - Routy, J‐P; Angel, JB; Patel, M; Kanagaratham, C; Radzioch, D; Kema, I; Gilmore, N; Ancuta, P; Singer, J; Jenabian, M‐A
<x xml:space="preserve">Abstract</x> Objectives Chloroquine (CQ), an anti‐inflammatory drug, inhibits Toll‐like receptor (TLR) signalling in plasmacytoid dendritic cells (pDCs) and may be beneficial for HIV‐infected patients in whom immune activation persists despite effective antiretroviral therapy (ART). The effect of CQ on CD4 T‐cell recovery and immune activation in immune nonresponding patients receiving successful ART was therefore studied. Methods Nineteen adults on ART with CD4 counts ≤350 cells/μL and undetectable viral load (VL) orally received CQ at 250 mg/day for 24 weeks. Side effects, CD4 and CD8 T‐cell counts, VL, T‐cell activation, pDC proportion and plasma inflammatory markers were assessed at baseline, at 24 weeks, and at 12 weeks after CQ discontinuation (clinicaltrial.org registration #NCT02004314). Results CQ was well tolerated and all patients maintained an undetectable VL. The absolute CD4 and CD8 T‐cell counts and their percentages, the pDC proportion, T‐cell activation, D‐dimer and C‐reactive protein (CRP) plasma levels and the kynurenine/tryptophan ratio did not change with CQ treatment. Among nine cytokines/chemokines measured, only levels of interferon (IFN)‐α2 were significantly increased by CQ treatment. Conclusions CQ was well tolerated in patients with low CD4 T‐cell counts despite long‐term effective ART; however, 24 weeks of CQ treatment did not improved CD4 T‐cell recovery, lymphoid and myeloid immune activation or inflammatory markers.